Dynamic strength training intensity in cardiovascular rehabilitation: is it time to reconsider clinical practice? A systematic review. (September 2019) - Hansen, Dominique; Abreu, Ana; Doherty, Patrick; Völler, Heinz
When added to endurance training, dynamic strength training leads to significantly greater improvements in peripheral muscle strength and power output in patients with cardiovascular disease, which may be relevant to enhance the patient's prognosis. As a result, dynamic strength training is recommended in the rehabilitative treatment of many different cardiovascular diseases. However, what strength training intensity should be selected remains under intense debate. Evidence is nonetheless emerging that high-intensity strength training (≥70% of one-repetition maximum) is more effective to increase acutely myofibrillar protein synthesis, cause neural adaptations and, in the long term, increase muscle strength, when compared to low-intensity strength training. Moreover, multiple studies report that high-intensity strength training causes fewer increments in (intra-)arterial blood pressure and cardiac output, as opposed to low-intensity strength training, thus potentially pointing towards sufficient medical safety for the cardiovascular system. The aim of this systematic review is therefore to discuss this line of evidence, which is in contrast to current clinical practice, and to re-open the debate as to what dynamic strength training intensities should actually be applied.